Characterisation of outgassing contact materials for miniature relays - Koller, Lidija (Informacije MIDEM, 1994)
Systematic investigations of vacuum outgassing for hermetic relays with AgCdO/AGPHOR and PdAg3O Au electroplated contacts were done. The experimental vacuum system constructed and built at our institute was additionally equiped with quadrupole mass spectrometer for residual gas analysis. Prior to the final encapsulation the relays were baked at the constant temperature of 125°C and outgassed in vacuum 1X10sup-5 mbar for several hours. The residual atmosphere was analysed every hour; in residual gas mixture, hydrogen, carbon monoxide, carbon dioxide, water vapour and remanents of cleaning chemical agents (ethanol, trichlorethylene) and hydrocarbons were found. Residual gas analysis showed that the concentration of impurity gases depends on materials and their treatments in different technological phases.
Keywords: Electronika; elektronika; kontaktna upornost; lastnosti; materiali; releji; sestavni deli